Los señores de Xochimilco en 1548 - Carrasco, Pedro (Tlalocan, 2013)
Dr. Carrasco presents an early Colonial legal document from Xochimilco, near the Mexican capital, dealing with the lands and tribute due to the native lords of the three cabeceras into which the city was divided -Tepetenchi, Tecpan and Olac. The document is rich in information on sociopolitical and economic themes, in reference to both the early Colonial administration and the much discussed system of land tenure among the caciques in pre-Conquest times.